La imagen del “indio” en los debates de las Cortes de Cádiz (1810-1812) - Núñez Díaz, Francisco Bladimir (2018)
The present article tries to identify, within the political debates developed in the sessions of the Spanish Cortes (1810-1812), the imagined or constructed image of the American Indians. It is the crisis of the Spanish Monarchy that brings along much of the conceptual references that the later American republics will use to establish their political principles. Citizenship will be one of the most important political discussions in which a large part of the new independent nations will be involved, but it takes a particular note in those regions where the population has different characteristics that will generate a greater complexity. Those particular elements will be present in the debates Cortes. In this context, we dare to present the way in which the indigenous populations of America and in particular of Peru were seen. We find elements that will have a similar pattern in later decades where modernity still rests on ideas that limit indigenous inclusion.